KAJIAN PENERIMAAN BAHASA PEMROGRAMAN BERORIENTASI OBJEK BERBASIS OPEN SOURCE DENGAN PENDEKATAN TAM (TECHNOLOGY ACCEPTANCE MODEL) STUDI KASUS UNIVERSITAS BUDI LUHUR - Ita Novita (Universitas Budi Luhur, 2011)
The successful implementation of a technology becomes an important thing that must be considered. One of the factors that currently play an important role in the successful implementation and use of information technology is a factor the user. User's level of preparedness to receive the information technology has a major influence in determining the success or failure of implementation of these technologies. Budi Luhur University as one of the educational institutions that rely on the support of technology need to know about it. The purpose of this study is to assess the acceptance of the use of java programming language among students, the factors that influence the acceptance rate and the level of significance. Various types of object-oriented programming language based on open source. Java programming language was chosen because it is one programming language in use and included in the curriculum of Informatics Engineering Program Faculty of Information Technology. This study approaches the Technology Acceptance Model (TAM). Analytical techniques used in this study is Structural Equation Modeling (SEM), as well as data obtained from the study will be processed using the software AMOS. The results of this study is a model of acceptance of the java programming language and the factors that influence the level of acceptance.Keywords: Java, Technology Acceptance Model (TAM), Structural Equation Modeling (SEM)